SOSIALISASI DAN PEMBUATAN U-DITCH INOVASI BETON DENGAN LIMBAH PLASTIK DAN LIMESTONE DI CV. TUNGGAL TRI PERKASA - Pratiwi, Kholis Hapsari; Rahmi, Ardia Tiara; Kurnianingsih , Oktavia; Pradana , Canggih Gilang; Deni, Delista Putri; Alfianarrochmah , Ilma; Yanto, Fendi Hary (Jurnal Abdi Insani, 2024)
The business of making and selling U-ditch products has been carried out by CV. Tunggal Tri Perkasa since 2021. However, sales have not experienced a significant increase due to the increasingly expensive material costs for making U-ditch and price competition with other U-ditch manufacturers. U-ditch is precast concrete used to make water channels and is made from materials such as cement, sand, gravel and water. The aim and benefits of this service are to overcome these problems. The RG D3 Civil Engineering team seeks to provide solutions by collaborating on concrete innovation research that has been carried out to be applied to partner U-ditch products. The innovative concrete used uses Polypropylene Plastic (PP) instead of gravel and limestone instead of sand and cement to minimize production costs. The method used in this service is to socialize and directly manufacture U-ditch with innovative concrete. The proportions designed for the innovative concrete use 15% limestone and 5% PP plastic to obtain quality according to U-ditch standards. The results of this service activity after completing the questionnaire to partner members were that 90% understood the socialization activities and stages of making U-ditch. This activity provides knowledge about renewable innovations in concrete to be applied to U-ditch so that in the future partners can increase production results.